Dependence of emulsion FMD vaccine immunogenicity on immune status of pigs - D. A. Lozovoy; V. A. Starikov; D. V. Mikhalishin; A. V. Borisov (Ветеринария сегодня, 2018)
The paper demonstrates dependence of virus-neutralizing antibody production and emulsion FMD vaccine immunogenicity on administration of vaccines against different infectious porcine diseases. Optimum interval between the administrations of the emulsion FMD vaccine and vaccines against other porcine diseases was determined.